Factors associated with the perception of fear of COVID-19 in university students - Camille Francine Modena; Moisés Kogien; Samira Reschetti Marcon; Lauro Miranda Demenech; Frantielen Castor dos Santos Nascimento; Marcos Vítor Naves Carrijo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze the factors associated with the perception of fear of COVID-19 in Brazilian university students. Methods: this is an online, cross-sectional analytical study conducted at a Brazilian public university with 1,437 undergraduate students between September and November 2020. The Fear of COVID-19 Scale was used to measure the main construct. Data analysis was performed using Mann-Whitney U test, Cohen's r test and multiple linear regression analysis. Results: factors associated with fear of COVID-19 in university students were the variables biological sex, perception of good sleep quality, many days of access to information, not complying with social distancing, reporting sufficient hours of sleep, not having a partner, guidance sexual non-heterosexual, being in the risk group for COVID-19 and tobacco consumption. Conclusions: the study findings can contribute to the discussion about the weaknesses that the university population is experiencing in this pandemic period.